THE STATISTICAL PARABOLIC PROJECTION METHOD UNTUK FORECASTING DALAM PENERIMAAN MAHASISWA BARU UNIVERSITAS ISLAM INDRAGIRI DI MASA MENDATANG - Rifa'i, Ahmad (LPPM Press STIE Indragiri Rengat, 2019)
The purpose of this study is to help predict the number of prospective new students who will register in the academic year 2023/2024 until the academic year 2026/2027. The research method uses the Statistical Parabolic Projection Method with data on the number of new student registrations of UNISI (Indragiri Islamic University) Tembilahan over the past 7 years. Research Results Based on Research Equations   formed in predicting the number of new students who will register in the academic year period 2023/2024 are 651 students, 2024/2025 are 818 students, 2025/2026 are 1001 Students, 2023/2024 are 1200 Students. Suggestions for future researchers who are still in the same theme as this research can be compared with other methods so that the resulting output can be more precise and accurate.